Case report: MRI and CT imaging features of a melanocytic tumour affecting a cervical vertebra in an adult dog, and review of differential diagnosis for T1W-hyperintense lesions - Michaelidou, Elli Elizabeth; Kaczmarska, Adriana; Gutierrez-Quintana, Rodrigo; Morris, Joanna; Hammond, Gawain; Cloquell, Ana (Frontiers in Veterinary Science, 2024)
A 7-year-old Lhasa Apso presented with a history of left thoracic limb lameness and neck pain. Magnetic resonance imaging revealed a well-defined, extradural lesion hyperintense on T1-weighted (T1W) images and isointense on T2W and T2* images located at the left lamina of the C4 vertebra. Computed tomography showed an isoattenuating and contrast enhancing mass centered on the left C4 vertebral lamina with associated osteolysis. The mass was surgically debulked and histopathology revealed a malignant melanocytic tumour. The patient recovered completely and received radiotherapy and 3 doses of the melanoma vaccine as adjunctive treatment. Eighteen months following treatment, the patient presented with neck pain again but further investigations were declined at this stage and the patient was euthanised. To the author's knowledge, this is the first case report describing the imaging characteristics of a cervical extradural melanocytic tumour in a dog. This case illustrates the MRI and CT imaging features and treatment of a canine melanocytic tumour of a cervical vertebrae.